Network security threat prevention and control system of electric power monitoring systems for wind farm - Wei DING (Dianxin kexue, 2020)
The frequent occurrence of network security incidents on wind farms seriously threatens the safety of power plants and power grids.The network security risk of power monitoring system on wind farms was analyzed from five aspects,including structure security,system ontology,security management,security emergency and infrastructure physical security.In view of the existing security protection technology,a security threat prevention and control system was put forward to ensure the safe and stable operation of the power monitoring system of wind farms and power grid from four aspects of security protection,security monitoring,access control and security management.